A formação continuada pela via do Coordenador Pedagógico - Prado, Gilsete da Silva (2015)
This research has as its theme the work of the Pedagogical Coordinator (PC) and aims to contribute to the understanding the performance of this professional in school, especially in the process of continuing education of teachers. For this reason, a revision in the literature was made about the Pedagogical Coordinator function, official documents of state and local level, to survey the history of your assignments. The survey was conducted in a municipality in the metropolitan region of São Paulo through closed questionnaire and applied to characterize the group of Pedagogical Coordinators with data on age, sex, teaching time, training, time on the job; and a group discussion with this group. The discussion sought to find out whether the coordinators are in the role of a teacher trainer, consider the HTPC as continuing education space at school, and felt prepared for this function.The analysis of the research allowed us to understand the day by day in schools and led us to the conclusion that the pedagogical coordinators live with difficulties caused by the very adverse working conditions, such as change of function, lack of identity, the isolation of daily work, the deficiency in teacher training, too much bureaucratic work and the fragility of procedures for the conduct of collective works. Through this research we conclude that required the redefinition of the role of coordinators, for the work done by them as a teacher trainer can contribute positively to a better performance of teachers and therefore of the students, thus contributing to the construction of a democratic, inclusive and quality schools